EDUKASI MEDIA SOSIAL YANG CEPAT, KREATIF, DAN AMAN MELALUI DIGITAL TREASURE HUNT DI MADRASAH ALIYAH BINA INSANI - Novita Lestari Anggreini; Nia Ekawati (ASOSIASI IDEBAHASA KEPRI, 2026)
Research by Effendy and Oktiani (2024) shows that cybersecurity literacy is crucial for adolescents in dealing with online manipulation. Based on this urgency, the community service team held an interactive counseling session themed